Il Fantasma dell’Io. La massa e l’inconscio mimetico: The Phantom of the Ego: Modernism and the Mimetic Unconscious - Lawtoo, Nidesh (Mimesis Edizioni, 2018)
A ghost roams the modern world: "the ghost of the ego" With this sentence, Friedrich Nietzsche offers a diagnosis of the modern self that finds the royal road to the unconscious in mass imitation. In the footsteps of Nietzsche, modernist authors such as Joseph Conrad, DH Lawrence, Georges Bataille - read in dialogue with human sciences such as anthropology and psychoanalysis, research on hypnosis and mass psychology - question themselves about reflected mimetic phenomena that do not they are under the rational control of consciousness and are, in this sense, in-conscious. From identification to affective contagion, passing through sympathy and laughter, violence and magic, hypnosis and suggestion, the mimetic unconscious reveals how modernist authors make our concept of "I" new because they anticipate recent developments in neuroscience. They also offer us an out-of-date mirror to reflect critically on the becoming of our "I" as well as on the power of authoritarian leaders - past and present - to transform the mass subject into a copy or a "ghost of the ego"